Coordinated control of grid-following and grid-forming energy storage for virtual inertia response considering frequency modal characteristics - Hengning Yu; Liangzhong Yao; Shuai Liang; Jian Xu; Fan Cheng; Ming Wu (International Journal of Electrical Power & Energy Systems)
Grid-following energy storage (GFL-ES) and grid-forming energy storage (GFM-ES) will coexist for a certain period into the future as one of the frequency regulation resources in low-inertia power systems. However, differences in synchronization mechanisms and inertia implementation approaches lead to significant variations in frequency response characteristics between GFL-ES and GFM-ES. The modal characteristics of GFL-ES’s virtual support capability further complicate the coordination control. To address this issue, this paper proposes a coordinated control method of GFL-ESs and GFM-ESs for virtual inertia response considering frequency modal characteristics. First, the differences in virtual inertia support characteristics between GFL-ES and GFM-ES are analysed based on a unified structural model. Subsequently, a quantitative analysis is conducted to investigate the mapping relationship between the modal inertia of the GFL-ES and changes in the frequency nadir time as well as control parameters. Then, considering the system’s initial frequency change rate constraints and the remaining capacity of energy storage, the virtual inertia control parameters of GFL-ES and GFM-ES are coordinated and allocated based on the unified structure model to effectively balance the virtual inertia support power of energy storage systems with different characteristics. Finally, simulation results demonstrate that the proposed method can effectively coordinate GFM-ES and GFL-ES with varying response characteristics, ensuring that the total virtual inertia support capability meets the expected requirements, demonstrating strong adaptability.© 2017 Elsevier Inc. All rights reserved.